Competencias digitales en estudiantes de cuarto grado de secundaria en instituciones educativas del distrito de Iquitos 2021 en cuanto al sexo - Eguren Wong, Joyce (2023)
The objective of this study was to compare fourth year students’ level of digital competencies at public high schools in Iquitos district 2021 in terms of gender. This was comparative research with field study, contemporary transectional and univariate designs. The population consisted of 1520 students and a stratified sample of 239 students with proportional allocation, 130 female and 109 male students. Data gathering tool was a valid and reliable questionnaire. Results showed that female students slightly outperformed male students in digital competencies (64.16 > 62.94), being at the "creator" level. The same is true for the following two dimensions: Technological literacy (63.88 > 63.37) and Multimedia literacy (64.86 > 62.12), except for Information literacy dimension (51.18 > 50.45) which is at the "expert" level. In conclusion, there is no statistically significant difference in the level of digital competencies between female and male students in the study population as p-value was 0.148 > α = 0.05, rejecting the working hypothesis.